Fin & Lady [compact disc, unabridged] - Schine, Cathleen (Macmillan Audio, 2013)
It's 1964. Eleven-year-old Fin and his glamorous, worldly, older half sister, Lady, have just been orphaned, and Lady, whom Fin hasn't seen in six years, is now his legal guardian and his only hope. That means Fin is uprooted from a small dairy farm in rural Connecticut to Greenwich Village, smack in the middle of the swinging '60s. He soon learns that Lady, giddy, careless, urgent, and obsessed with being free, is as much his responsibility as he is hers.